Extensão popular: a pedagogia da participação estudantil em seu movimento nacional - Cruz, Pedro José Santos Carneiro (2010)
The present study analyzes the experiences of university extension in the perspective of Popular Education, called Popular Extension. Produced as the final result of the Master in Education course, this research had as its objective to analyze the pedagogical meaning of the student participation in the organization of the National Joint of Popular Extension (ANEPOP) in order to understand how participation in the movement contributes for the university formation of the students. The methodologies of research used have allowed to apprehend the inherent pedagogical aspects to this experience, providing its theoretical reading and its critical analysis to current discussions concerning student training and university reform. The construction of this research is the product of the active participation of the researcher experience. The research had access to the registers of the events and the different actions and resulting reactions, included personal comments, the informal exchanges and an effort of action research of qualitative character to rescue historically the experience and to undertake a critical analysis. The systematization of the experience of the ANEPOP allowed to better understand this movement and its dynamics. The ANEPOP demonstrates the political transformative force of the pedagogy of Popular Extension, defying the traditional models and announcing the necessary invention and reinforcement of new models. Moreover, at the same time that it agglutinates the students, as citizens, and it favors its organization politics and capacity of intervention, is offers greater visibility to the alternative of the methodology of Popular Extension. On the basis of this study, we could understand that this pedagogy has made possible significant contributions to the university training of these students. The uniqueness in this pedagogy of the ANEPOP is its capacity to insert the students in spaces of protagonist action with repercussions of national scope. Furthermore, it underlines the excellent knowledge, accumulated in the movement, of coexistence little exercised in the scope of the local projects of extension. An essential integration with the pedagogy apprehended in the projects of Popular Extension is evident in the incessant efforts these students to apply the Popular Education (so divulged and elaborated in its local projects) in their leadership of their national movement. Thus, Popular Education moves from being only a theoretical inspiration to being incorporated as an ethical and philosophical reference, as a horizon according to which these students search to guide and to lead its individual and collective action. To live deeply the national movement of popular extension is to evidence the vibrant expression of university and social actors of the permanent construction of the utopia of a Popular University, that is participative, libertarian, democratic, and loving. Popular Education is no longer something strange or quaint and becomes a matrix and a permanent source of inspirations to the university as an institution that gives meaning to the life of all the people.